Horizontally transferred genes in the ctenophore Mnemiopsis leidyi - Hernandez, Alexandra M; Ryan, Joseph F (PeerJ Preprints, 2018)
Horizontal gene transfer has had major impacts on the biology of a wide range of organisms from antibiotic resistance in bacteria to adaptations to herbivory in arthropods. A growing body of literature shows that horizontal gene transfer (HGT) between non-animals and animals is more commonplace than previously thought. In this study, we present a thorough investigation of HGT in the ctenophore Mnemiopsis leidyi. We applied tests of phylogenetic incongruence to identify nine genes that were likely transferred horizontally early in ctenophore evolution from bacteria and non-metazoan eukaryotes. All but one of these HGTs (an uncharacterized protein) are homologous to characterized enzymes, supporting previous observations that genes encoding enzymes are more likely to be retained after HGT events. We found that the majority of these nine horizontally transferred genes were expressed during development, suggesting that they are active and play a role in the biology of M. leidyi. This is the first report of HGT in ctenophores, and contributes to an ever-growing literature on the prevalence of genetic information flowing between non-animals and animals.
Keywords: evolution; lateral gene transfer; hypothesis testing; phylogenetics